Adapting Jobs Policies and Programs in the Face of Accelerated Technological Change - Saliola, Federica; Mohamed Islam, Asif; Winker, Hernan (World Bank, Washington, DC, 2020)
This Jobs Solutions Note identifies approaches for practitioners and policymakers to proactively adapt policies and development programs to accelerated technological change. Based on curated knowledge and emerging evidence for a specific topic and relevant to jobs, the Jobs Solutions Notes are not intended to be exhaustive; they provide key lessons, solutions and approaches synthesized from the experiences of the World Bank Group and partners. This Note draws from World Development Report 2019: The Changing Nature of Work and Protecting All: Risk-Sharing for a Diverse and Diversifying World of Work.